Membangun Interaksi Karitatif Kaum Muda Katolik kepada Penyandang Disabilitas - Edita Tersa Risa (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
People with disabilities or disabilities, who are often also called people with disabilities, actually have equal opportunities in all aspects of life. This aspect is not only a matter of social rehabilitation or social assistance, but concerns all aspects of life related to the rights of persons with disabilities. however, the reality is that people with disabilities often do not enjoy the same opportunities as other people. Various facts show that there is unfair and discriminatory treatment that is still often experienced by Persons with Disabilities when meeting their basic needs. Negative stigma has interpreted persons with disabilities as synonymous with people who are sick, weak, helpless, and only burden other people. This fact makes persons with disabilities need special attention which is the responsibility of and involves all parties, including the government, society and the Church, including Catholics. Catholic young people are the future of the Church, therefore young people need to be prepared to assume responsibility for the future of the Church and their nation. Youth and youth are not the only target of the Church's concern. They are also actors of Evangelization and social renewal. They make up half of all God's people. They are sensitive to the values ​​of justice, peace, brotherhood, friendship, solidarity, and so on. But they are also burdened with restlessness, deception, restlessness and fear, again temptations. In them to instill respect for everyone, love for neighbor, justice, the habit of prayer and love of purity. As one of OMK's goals, namely love for others, persons with disabilities are an important part of the perspective of young Catholics (OMK). People with disabilities basically have the same living conditions as other humans. They have problems, needs, and are entitled to their rights as other citizens.